Kant and Husserl on the Contents of Perception. Issue 2 (June 2016) - van Mazijk, Corijn
ABSTRACT: This paper focuses on the contents of perception in Kant's first Critique and Husserl's later writings. Both Kant and Husserl are known for their appeal to synthesis in their transcendental accounts of perceptual experience and objective judgment. Especially regarding Kant, the precise nature of perceptual synthesis has recently been the cause of much debate. Whereas some argue that for Kant perception must have nonconceptual content, others believe he is a conceptualist. After offering an alternative solution to this interpretative problem in Kant's philosophy, I turn to Husserl's later theory of perception. My main claims here are that Husserl departs from Kant specifically regarding (i) the sort of synthetic contents that govern affective perception and (ii) the role of conceptual capacities in the contents of attentive perception.